2018
DOI: 10.1101/354357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A tradeoff between tolerance and resistance to a major fungal pathogen in elite wheat cultivars

Abstract: Tolerance and resistance represent two strategies that hosts evolved to protect themselves from pathogens. Tolerance alleviates the reduction in host fitness due to infection without reducing a pathogen's growth, while host resistance reduces pathogen growth. We investigated tolerance of wheat to the fungal pathogen Zymoseptoria tritici in 335 elite wheat cultivars. Using a novel digital phenotyping approach involving 11152 infected leaves, we discovered a new component of tolerance operating on individual lea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 74 publications
(14 reference statements)
0
8
0
1
Order By: Relevance
“…ρ leaf represents the overall reproductive success per area while ρ lesion focuses on the reproductive success within the lesion area. Tolerance indicates the ability of the host to tolerate pathogen reproduction while limiting damage by lesions (Mikaberidze & McDonald, 2020). We found that the mean pycnidia count ranged from 0-20 (mean 7, median 6.3) among isolates and PLACP ranged from 2-97 % (mean 56%, median 57.7%) (Fig.…”
Section: Heritability and Correlations Among Pathogenicity Traitsmentioning
confidence: 83%
See 1 more Smart Citation
“…ρ leaf represents the overall reproductive success per area while ρ lesion focuses on the reproductive success within the lesion area. Tolerance indicates the ability of the host to tolerate pathogen reproduction while limiting damage by lesions (Mikaberidze & McDonald, 2020). We found that the mean pycnidia count ranged from 0-20 (mean 7, median 6.3) among isolates and PLACP ranged from 2-97 % (mean 56%, median 57.7%) (Fig.…”
Section: Heritability and Correlations Among Pathogenicity Traitsmentioning
confidence: 83%
“…Furthermore, variation in the pathogen's ability to spread across tissue and manipulate host immune responses could also lead to variation in overall lesion development. Interestingly, extensive lesion development is not necessarily related to pycnidia production by the pathogen across cultivars (Karisto et al, 2018;Mikaberidze & McDonald, 2020). This suggests that despite damage to the leaf, the host immune system can e ciently repress the pathogen from acquiring nutrients to reproduce.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, variation in the pathogen's ability to spread across tissue and manipulate host immune responses could also lead to variation in overall lesion development. Interestingly, extensive lesion development is not necessarily related to pycnidia production by the pathogen across cultivars (Karisto et al, 2018;Mikaberidze & McDonald, 2020). This suggests that despite damage to the leaf, the host immune system can efficiently repress the pathogen from acquiring nutrients to reproduce.…”
Section: Discussionmentioning
confidence: 98%
“…rleaf represents the overall reproductive success per area while rlesion focuses on the reproductive success within the lesion area. Tolerance indicates the ability of the host to tolerate pathogen reproduction while limiting damage by lesions (Mikaberidze & McDonald, 2020). We found that the mean pycnidia count ranged from 0-20 (mean 7, median 6.3) among isolates and PLACP ranged from 2-97 % (mean 56%, median 57.7%) (Fig 1C, We estimated SNP-based heritability (h 2 snp) for each trait using a genomic-relatedness-based restricted maximum-likelihood approach to partition the observed phenotypic variation (Fig 1D).…”
Section: Heritability and Correlations Among Pathogenicity Traitsmentioning
confidence: 99%
“…(Kefauver et al, 2015). As aplicações de imagens de órgãos de plantas são comuns na literatura e inclusive utilizadas para mensurar a tolerância de plantas a doenças (Mikaberidze e McDonald, 2018).…”
Section: Fenotipagem De Alto Rendimento No Melhoramento De Plantasunclassified